Iron Dagger, East Langton (Proceedings of the Society of Antiquaries of Scotland, 1852)
Dr. Daniel Wilson's description of the discovery of an iron dagger and a knife found on a farm in Kirknewton is reprinted from his Prehistoric Annals of Scotland. The weapons along with a few other other artifacts were found 3.5 feet below the surface when farmhands were draining a field. Wilson notes that these artifacts are all characteristic of the last pagan period in Scotland. The artifacts were donated to the Society.